Cover Feature: Cellulose Depolymerization with LPMO‐inspired Cu Complexes (ChemCatChem 22/2021). Issue 22 (28th October 2021) - Castillo, Ivan; Torres‐Flores, Andrea P.; Abad‐Aguilar, Diego F.; Berlanga‐Vázquez, Armando; Orio, Maylis; Martínez‐Otero, Diego
Abstract : The Cover Feature represents the oxidative depolymerization of cellulose, affording cellobiose, levoglucosan, and gluconic acid as water‐soluble products. In their Communication, I. Castillo et al. present the catalytic depolymerization of cellulose with copper complexes inspired by fungal and bacterial Lytic Polysaccharide Monooxygenase enzymes. The use of hydrogen peroxide as oxidant boosts the consumption of insoluble cellulose, resulting in soluble products that were separated by HPLC and identified based on ESI‐MS data. Experimental evidence of a cupric hydroperoxo reactive intermediate is supported by DFT calculations, providing insight on the use of recalcitrant biomass. More information can be found in the Communication by I. Castillo et al.